Implementation of Public Transportation Policy from the Perspective of Siyasah Tanfidziyyah in Bandar Lampung City - Wibowo, Thoriq Adrian; Faizal, Liky; Latua, Abidin (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
This study examines the implementation of public transportation policies in Bandar Lampung City based on Regional Regulation Number 10 of 2017 through the perspective of Fiqh Siyasah Tanfidziyyah. The main problem studied is the lack of adequate provision of public transportation even though it has been regulated in Regional regulations, especially regarding the obligation of the Regional government to guarantee the availability of public transportation as stipulated in Article 89 Paragraph (1). This study uses a juridical-normative and juridical-empirical approach with data collection techniques through in-depth interviews, field observations, and documentation studies at the Bandar Lampung City Transportation Agency. The results of the study indicate that the implementation of public transportation policies has not been running optimally due to budget limitations, minimal coordination between stakeholders, and low commitment to implementing regulations. The analysis of Fiqh Siyasah Tanfidziyyah reveals that the government as ulil amri has constitutional and sharia responsibilities in realizing public welfare through the provision of safe, comfortable, and affordable transportation facilities. This study recommends the need to revitalize the public transportation system through strengthening regulations, increasing budget allocations, and implementing good governance principles in line with Islamic values.